2012
DOI: 10.1515/ijdhd-2012-0032
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of substance use behaviours and normative beliefs in North-West European university and college students

Abstract: The social norms approach is an increasingly popular intervention for substance use that has been used extensively in the American college system. It operates by correcting normative misperceptions individuals hold about their peers. However, there have been few direct comparisons of substance use misperceptions between student populations in different European countries. The current study sought to address this through use of a survey of substance use and normative beliefs at universities in fi ve European co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Within the European Union population, university and college students demonstrate hazardous rates of substance use (Akmatov et al, 2011;Karam et al, 2007;McAlaney et al, 2012;Stock et al, 2009). Research on European students is limited in comparison to the work that has been done on substance use among students in the American college system (Wicki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Within the European Union population, university and college students demonstrate hazardous rates of substance use (Akmatov et al, 2011;Karam et al, 2007;McAlaney et al, 2012;Stock et al, 2009). Research on European students is limited in comparison to the work that has been done on substance use among students in the American college system (Wicki et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The self-report survey instrument was developed through consultation of the literature and previous social norms surveys [21,24]. Surveys were paper-based and responses were obtained using a multiple choice, tick-box-style format.…”
Section: Methodsmentioning
confidence: 99%
“…Perceptions of group norms surrounding a particular behaviour consistently show strong positive associations with self-reports of engagement in and permissiveness towards that behaviour, with those with higher reported norms perceiving norms to be particularly high [20]. These effects have been identified in a broad a range of behavioural domains, including alcohol consumption [17,18,19], gambling [21], risky sex [22], seatbelt use [23], substance use [24], and snacking behaviour [25]. A relatively small number of studies have found no direct relationship between perceived norms and individuals’ own behaviour, but where this is the case, samples may be small and the reference groups unspecific and distal [26], or norms do predict behaviour but only under particular conditions [27].…”
Section: Introductionmentioning
confidence: 99%
“…The work which has been done in the UK and Europe suggests that similar misperceptions of substance are evident in European student populations (McAlaney and McMahon 2007;McAlaney et al 2012;Page et al 2008), however there remains a need to further determine the nature of these misperceptions within UK students, particularly as the social norms approach becomes more popular in Europe (McAlaney et al 2011). It cannot be assumed that research developed in the American college system is applicable to European settings, given the differences in legislation, culture and educational systems (Wicki et al 2010).…”
Section: Introductionmentioning
confidence: 99%